Analisis Kepuasan Pengguna Audience Insights Menggunakan Model Sosial Strategis CRM - Tetuko Aldimas Setyawan Eka Pradana; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Highly competitive market conditions, unexpected changes in consumption trends and increasingly complex customer demands require business actors to deliver products / services that meet market needs. One way to be able to know the products / services in accordance with market conditions is to communicate directly with customers. Audience Insights is one of the CRM tools on Facebook that focus on the operational field. This study aims to determine the satisfaction of sellers when they use Audience Insights as a medium to do promotion using strategic social model of CRM. The model has five indicators: customer relationship oriented, social media technology use, customer engagement initiatives, relational information processes and customer relationship performance. The sample of this study amounted to 86 data with an age range between 17 - 44 years of domicile in Malang. The results of the study indicate that all indicators have a good and acceptabel level of significance. Variables of social media technology use, customer engagement initiatives, and relational information processes have strong relationships. Customer relationship performance variable has moderate relationship and customer relationship oriented variable has no relationship.